Lower Funneling Pathways in Scedosporium Species - Poirier, Wilfried; Ravenel, Kevin; Bouchara, Jean-Philippe; Giraud, Sandrine (Frontiers in Microbiology, 2021)
Lignin, a natural polyaromatic macromolecule, represents an essential component of the lignocellulose biomass. Due to its complexity, the natural degradation of this molecule by microorganisms still remains largely misunderstood. Extracellular oxidative degradation is followed by intracellular metabolic degradation of conserved aromatic intermediate compounds (protocatechuate, catechol, hydroxyquinol, gentisic acid) that are used as carbon and energy sources. The lower funneling pathways are characterized by the opening of the aromatic ring of these molecules through dioxygenases, leading to degradation products that finally enter into the tricarboxylic acid cycle. In order to better understand the adaptation mechanisms of Scedosporium species to their environment, these specific catabolism pathways were studied. Genes encoding ring-cleaving dioxygenases were identified in Scedosporium genomes by sequence homology and a bioinformatic analysis of the organization of the corresponding gene clusters was performed. In addition, these predictions were confirmed by evaluation of the expression level of the genes of the gentisic acid cluster. When the fungus was cultivated in the presence of lignin or gentisic acid as sole carbon source, experiments revealed that the genes of the gentisic acid cluster were markedly overexpressed in the two Scedosporium species analysed (Scedosporium apiospermum and Scedosporium aurantiacum). Only the gene encoding a membrane transporter was not overexpressed in the gentisic acid-containing medium. Together, these data suggest the involvement of the lower funneling pathways in Scedosporium adaptation to their environment.